Review of the American genus Bolostromus Ausserer, 1875 with the description of fourteen new species (Araneae, Cyrtaucheniidae) - Dupérré, Nadine (Zootaxa, 2023)
The family Cyrtaucheniidae is seldom found in the Americas, only 10 species are known to occur. Herein we described fourteen new species for the family Cyrtaucheniidae, all belonging to the genus Bolostromus from Central America and South America: Bolostromus busu n. sp. (female); B. devriesi n. sp. (female); B. epiphyticus n. sp. (male, female); B. fonsecai n. sp. (male); B. hubeni n. sp. (male, female); B. italoi n. sp. (female); B. laheredia n. sp. (male); B. losrios n. sp. (male); B. nischki n. sp. (male); B. urku n. sp. (male), B. primus n. sp. (male); B. pristirana n. sp. (male); B. stridulator n. sp. (male), and B. valdivia n. sp. (female). Photographs of the type specimens of: Bolostromus fauna (male and female); Bolostromus gaujoni (male); B. holguinensis (female juvenile); B. insularis (female juvenile); B. pulchripes (female); B. riveti (male) and, B. venustus (female) are provided, as well as a distribution map of all species.